Juizado criminal: uma crítica à transação penal diante da tensão entre garantismo e eficiência do procedimento - Souza, Ailton Alfredo de (2010)
This dissertation investigates the legal institute of the penal transaction applied within the grounds of the Special Criminal Court and its relation with the constitutional principles that guarantee fundamental rights for the citizens in the legal process area. It will be studied the correlation between the concepts of process and procedure and the practice of each procedural act which culminates in the penal transaction: since the transcription of the Detailed Occurrence Term by the police authority to the Preliminary Hearing. The starting point of this investigation is the eventual tension between the legal process principles which is a way of guaranteeing the legal jurisdiction service and the search for efficiency of the penal jurisdiction service as a way of undermining the legal guarantees due to the imbalance of this equation in the current practice of the penal transaction. The investigation starts from a bibliographical revision about the subject and also the analysis of statistical data about the typology of the occurrences and the nature of the legal sentences handed down in the year of 2009 in the Special Criminal Court of the State of Pernambuco. Samples of real cases submitted to the criminal courts are analyzed in order to confront the praxis of the penal transaction with the legal process principles used as basis for that matter. This research demonstrate the existence of the imbalance between garantism and efficiency in the praxis of the Penal Transaction in Brazil and it proposes the basis to materialize this institute together with the constitutional process principles, specially the principle of the due process of law and its corollaries of the wide defense and contradictory.